EVALUATION OF HAJJ FUND MANAGEMENT IN INDONESIA - Muhammad Iqbal Jafar; Laode Rudita (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
Hajj fund management in Indonesia is crucial for sustainable Hajj financing and for improving Hajj service quality for pilgrims. This article aims to strengthen policy evaluation and evaluation planning for Hajj fund management by placing accountability at the center of public governance. A persistent problem is how investment returns and investment risk management translate into fair, transparent, and efficient financing outcomes. Using a conceptual literature review and policy document analysis, the study designs an evaluation plan for Badan Pengelola Keuangan Haji. The approach follows the Evaluation Planning and Implementation Cycle model and structures an evaluation planning matrix. The results show that process and implementation evaluation is the most actionable entry point for improving Hajj fund governance. Priority evaluation domains include investment policy, portfolio performance, and risk controls; allocation rules between program costs, benefit returns, and reserves; transparency, disclosure, and public reporting; stakeholder participation, grievance handling, and service responsiveness; compliance with Islamic finance principles; procurement integrity and operational efficiency; and coordination among supervisory, audit, and regulatory institutions. Recommended indicators combine financial returns, risk exposure, compliance, timeliness of reporting, and stakeholder satisfaction, using portfolio data, audited statements, and stakeholder feedback. The planning matrix links each question to data sources, analytic methods, and responsible actors, enabling timely feedback to improve processes and prevent misuse. It also clarifies trade offs between risk tolerance, returns, and affordability. Overall, systematic evaluation planning improves accountability, safeguards long term sustainability, and strengthens public trust in Hajj fund management Indonesia, while providing a practical roadmap for continuous service improvement.